2005
DOI: 10.1177/0273475305276624
|View full text |Cite
|
Sign up to set email alerts
|

Social Styles of Students and Professors: Do Students’ Social Styles Influence Their Preferences for Professors?

Abstract: This article uses Merrill and Reid’s classification of social styles as drivers, analyticals, expressives, and amiables to examine differences between the personalities of different business majors and student choices of favorite professors. Significant differences were found in the social styles of different business majors. Furthermore, one’s major interacted with his or her gender to have a significant effect on the student’s social style. Students relied on cues both inside and outside the classroom to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 19 publications
0
31
0
3
Order By: Relevance
“…Students in this group also made recommendations to the tutor as to how they might undertake the final tutorial review session prior to the final exam suggesting that there had been a change in the leadership ability of students within this group, or perhaps indicating a re-focusing of the strong personalities within the group. The nature of the impact of teacher personalities, leadership ability of students and their impact upon group dynamics has already been highlighted in the education literature and deserves further investigation (Schlee, 2005) In the final evaluation of this action research project, assessing changes to learning style proved difficult. Due to the necessity for anonymity, the direct assessment of changes in individual learning styles was unable to be assessed.…”
Section: Results and Reflectionmentioning
confidence: 90%
See 3 more Smart Citations
“…Students in this group also made recommendations to the tutor as to how they might undertake the final tutorial review session prior to the final exam suggesting that there had been a change in the leadership ability of students within this group, or perhaps indicating a re-focusing of the strong personalities within the group. The nature of the impact of teacher personalities, leadership ability of students and their impact upon group dynamics has already been highlighted in the education literature and deserves further investigation (Schlee, 2005) In the final evaluation of this action research project, assessing changes to learning style proved difficult. Due to the necessity for anonymity, the direct assessment of changes in individual learning styles was unable to be assessed.…”
Section: Results and Reflectionmentioning
confidence: 90%
“…This tutor had a more outgoing personality than the other tutor and had greater success in reducing the degree of external regulation in class activities. While this may have been attributed to teaching style, it may also be a function of the individual's personality as some current research suggests (for example, Schlee, 2005). The situation may also have arisen as the result of the social styles or personalities of students within the group (Clark & Trow, 1966).…”
Section: Results and Reflectionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the latter findings are debatable. Consistent with this thinking, Schlee (2005) found that 53% of management majors prefer work that is characterized as ambitious and egotistical, yet friendly. Similarly, Gilbert et al (2008), in a sample of 975 graduating seniors, found that those who had work preferences for leading others, controlling others, and moving up the career ladder also demonstrated a high interest for working in jobs related to management.…”
Section: Information Technology Majorsmentioning
confidence: 67%